Predictors of sleepiness in a large-scale epidemiology study ESSE-RF - Bochkarev, Mikhail; Korostovtseva, Lyudmila; Rotar, Oxana; Verbitskaya, Elena; Sviryaev, Yurii; Zhernakova, Yulia; Shalnova, Svetlana; Konradi, Alexandra; Chazova, Irina; Boytsov, Sergey; Shlyakhto, Evgeny (Frontiers in Neurology, 2024)
Introduction To identify predictors of excessive daytime sleepiness we analyzed data from the ‘Epidemiology of cardiovascular diseases in regions of Russia (ESSE-RF)’ study. Methods Data from participants of the cohort study ESSE-RF (2012–2013), aged 25–64 years, from 13 regions of Russia were analyzed (2012–2013). The participants were interviewed regarding their sleep complaints, including difficulties with initiating and maintaining sleep, sleepiness, and use of sleeping pills. Sleepiness was considered significant if it occurred at least three times a week. The examination encompassed social, demographic, and anthropometric measures, lifestyle factors, self-reported diseases, and laboratory parameters. The final analysis included 13,255 respondents. Results Frequent (≥3 times/week) sleepiness was reported by 5,8%, and occasional sleepiness (1–2 times/week) by 10.8% of respondents. Multivariate regression analysis identified significant predictors of frequent sleepiness. Sleep complaints (insomnia, sleep apnea, snoring) and frequent use of sleep medication were prominent factors. Additionally, age, female gender, higher education, and retirement status were associated with sleepiness. Beyond demographics and sleep, the analysis revealed predictors: abnormal anxiety levels, low high-density lipoprotein, high salt intake and following medical conditions: arrhythmia, hypertension, myocardial infarction, other heart diseases, and renal disease. Conclusion This study identified a significant prevalence of EDS in Russians, aligning with global trends. However, findings suggest potential regional variations. Analysis revealed a complex interplay of factors contributing to EDS, highlighting the importance of individualized treatment approaches for improved sleep health.